Microstructure and mechanical properties of mechanically alloyed ODS copper alloy for fusion material application. (May 2018) - Aghamiri, S.M.S.; Oono, N.; Ukai, S.; Kasada, R.; Noto, H.; Hishinuma, Y.; Muroga, T.
Highlights: A new ODS copper alloy including 0.42wt%Y2 O3 particles was developed successfully by MA method. MA resulted in decrease of crystallite size and increment of dislocation density and hardness. Fine semicoherent Y2 O3 particles were distributed with an average size of 10.8 nm and spacing of 152 nm. The annealed ODS copper alloy showed a yield strength of 272 MPa and total elongation of 12%. Abstract: Advanced oxide dispersion strengthened copper alloys are promising structural materials for application in divertor system of future fusion reactors due to high irradiation resistance, high thermal conductivity, and good mechanical properties. In this study, a new ODS copper including 0.42wt%Y2 O3 nanosized oxide particles was developed successfully by mechanical alloying method using addition of 1 wt% Stearic acid in Ar atmosphere. Mechanical alloying resulted in decrease of crystallite size to 28 nm in concurrent with increment of dislocation density and hardness to the saturated level of 1.7 × 10 15 m − 2 and 226HV0.1 after 48 h milling, respectively. Consolidated ODS copper by SPS and then hot roll-annealing at 900 °C/60 min showed an average grain size of 1.1 µm with a near random texture. Furthermore, TEM observations demonstrated fine semicoherent Y2 O3 oxide particles distributed with a misfit parameter ( δ ) of 0.17 in copper matrix with an average size of 10.8 nm and interparticle spacing of 152 nm. Finally, tensile test evaluation determined comparable mechanical properties of the annealed ODS copper (Cu-0.42wt%Y2 O3 ) with Glidcop-Al25 including a yield strength of 272 MPa and total elongation of 12%, by two mechanisms of grain boundary strengthening and oxide particle strengthening.